A comparative study of adhesion by bacterial isolates of marine origin. (September 2017) - Rodríguez-Calvo, Alfonso; Silva-Castro, Gloria Andrea; Uad, Imane; Robledo-Mahón, Tatiana; Menéndez, Mateu; González-López, Jesús; Calvo, Concepción
Abstract: Extracellular polymeric substances (EPS) are one of the main components of microbial biofilms, which are markedly influenced by the chemical composition and functional properties of these EPS. This study quantified the adherence capacity of 29 bacterial strains isolated from marine water in Luria–Bertani and Bushnel-Haas culture media. Their capacity to produce EPS and the influence of the culture conditions on the chemical composition and emulsifying activity of their synthesised exopolymers was determined. Eighteen of the bacterial strains in this study produced EPS while eleven were unable to do so. Surface adherence was associated with bacterial growth and with the capacity of the isolates to synthesise EPS. Pseudoalteromonas elyakovii W18 showed the highest values for surface adherence and synthesised a non-bioemulsifier EPS. Principal component analysis (PCA) was used to establish the relationships between the biopolymer characteristics and surface adherence. The efficient adherence of P elyakovii on the surface of K1 (Anoxkaldnes © ) carrier was confirming by scanning electronic microscopy. Highlights: Surface adherence was associated with bacterial growth and Exopolymer production. Characteristics of Exopolymers influence the surface adherence of bacteria. P. elyakovii W18 is a good candidate to form biofilms for bioremediation uses.